Indian rural sociology - Sharma, R.N. (Kanpur, 1966)
Hardly an apology is needed for a sociological analysis of rural community, rural social change, rural social problems, community development projects and rural welfare in India. The author has only tried to fall the long felt need of an all round brief text book for the students of Indian rural sociology. The books hitherto written have been confined to this or that aspect of rural life. The present book is different because of its all round perspective. And yet many things could not be men tioned, many points have remained too brief because of limita tions of space. Thus while this book will serve as an introdu ctory course, for details the reader should persue books, reports and periodicals mentioned in the bibliography. The author will most thankfully acknowledge all suggestions for improvement.
Keywords: Sociology